2011
DOI: 10.1007/s12600-011-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Beauveria bassiana and Metarhizium anisopliae against Galleria mellonella

Abstract: The greater wax moth Galleria mellonella L. (Lepidoptera: Pyralidae) is occasionally found in beehives and is a major pest of stored wax. Entomopathogenic fungi have recently received attention as possible biocontrol elements for certain insect pests. In this study, 90 isolates of Beauveria bassiana and 15 isolates of Metarhizium anisopliae were screened for proteases and lipases production. The results showed significant variations in the enzymatic action between the isolates. In the bioassay, the selected is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
4
18
0
3
Order By: Relevance
“…bassiana has been reported as a biological control agent against insects. 9,28 In this study, reductions in larval population increased with time following B. bassiana application, with the wileyonlinelibrary.com/journal/ps maximum reduction at 7 DPA. These results correspond to the results of earlier studies that found that insects infected with B. bassiana died within 3-5 days of hyphal penetration.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…bassiana has been reported as a biological control agent against insects. 9,28 In this study, reductions in larval population increased with time following B. bassiana application, with the wileyonlinelibrary.com/journal/ps maximum reduction at 7 DPA. These results correspond to the results of earlier studies that found that insects infected with B. bassiana died within 3-5 days of hyphal penetration.…”
Section: Discussionsupporting
confidence: 49%
“…B. bassiana has been reported as a biological control agent against insects . In this study, reductions in larval population increased with time following B. bassiana application, with the maximum reduction at 7 DPA.…”
Section: Discussionmentioning
confidence: 55%
“…These finding probably indicated the degradation of the epicuticle of the host caused by pathogens which entered through the sites of penetration (Vestergaard et al, 1999;Arruda et al, 2005;Zhang et al, 2010;Yan et al, 2011). The cuticle of the Galleria mellonela (Lepidoptera: Pyralidae) larvae infected with M. anisopliae and B. bassiana became black-spotted due to excessive melanization, indicating direct attack of the fungus on the defense system of the insects (Hussein et al, 2012).…”
Section: Morphological Alterations In the Cuticle Of The Pupae Of D mentioning
confidence: 99%
“…In the pupal stage, the insect does not eat and can be affected by entomopathogenic fungi that penetrate through the cuticle. Several orders of insects such as Diptera, Coleoptera, and Thysanoptera are infected in their pupal stage (Watt and Lebrun, 1984;Ekesi and Maniania, 2000;Destéfano et al, 2005;Ansari et al, 2007); however, the infection and colonization mechanism of the pathogen in this stage has been described a little in Lepidoptera, but has not been demonstrated in larvae (Revathi et al, 2011;Hussein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported by another authors differences among lethal times is a tool widely used in selecting strains, because it is interesting that the fungus quickly eliminate its host, as well [13]. These results are disagreed with Khalid et al [14], evaluating the virulence of various strains of B. bassiana and M. anisopliae on G. mellonella larvae using 10 2 , 10 3 , 10 4 , 10 5 and 10 6 conidia ml -1 concentration.…”
Section: Discussionmentioning
confidence: 87%